Emerging transnational corporations : an economic power or a transitional phenomenon? - Ong, Joo Hua. (2009)
The economies of South-East Asia are typically transformed by the investments of foreign multinationals. Now these economies are being guided by their own home-grown conglomerates. Based on ten case companies, this paper seeks to understand the nature of these emerging transnational corporations (ETNCs) and how they differ from the traditional transnational corporations (TTNCs) from Japan, United States and Europe.